Pengaruh Kompetensi Keselamatan Pasien terhadap Aktivitas Keselamatan Pasien dan Penilaian Kinerja Perawat - Prasetyo, Yuda Dwi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Patient safety is a crucial issue in healthcare services worldwide. Various safety incidents, including Adverse Events (AEs), Near Misses (NMs), and No Harm Incidents (NHIs), frequently occur and pose serious risks to patients. This study aims to examine the influence of patient safety competence on patient safety activities and nurse performance assessments. The method used is a literature review, which systematically examines relevant journal articles on patient safety and nurse performance. The selected articles were published between 2020 and 2024 and were sourced from electronic databases such as Google Scholar, PubMed, and Springer. Search keywords included